DIFFERENTIAL DIAGNOSIS OF DISEASES ACCOMPANIED BY PROLONGED FEVER IN CHILDREN - Javlon Mamanazirov; Numon Valiyev (Modern American Journals, 2025)
Prolonged fever in children, defined as a fever lasting more than 10–14 days, presents a diagnostic challenge in pediatric practice. A variety of infectious, inflammatory, neoplastic, and autoimmune diseases may underlie such presentations. This study aims to analyze common causes of prolonged fever in children, identify key clinical and laboratory markers, and propose an evidence-based approach for differential diagnosis. A retrospective analysis of 120 pediatric cases with fever lasting more than two weeks was conducted. Findings indicate that infections (particularly tuberculosis and Epstein-Barr virus), connective tissue diseases (e.g., juvenile idiopathic arthritis), and malignancies (e.g., leukemia) are among the most frequent etiologies. Early differentiation through targeted investigations significantly reduces diagnostic delays and improves clinical outcomes.